MYTHS AND PLACES ([S.l.])
1 online resource
Keywords: This volume explores the dialogic relationship between myths and places in the historically, geographically, and culturally diverse context of India. Given its ambiguous relationship with facts' and empirical reality, myth has suffered an uncertain status in the field of professional history, with the latter's preference for scientifism over more creative orders of representation. Myths and Places rehabilitates myth, not as history's primeval Other', nor as an instrument of socio-religious propagation, but as communitarian mechanisms by which societies made sense of themselves and their world. It argues that myths helped communities fashion their identities and their habitat/habitus, and were fashioned by these in turn. This book explores diverse forms of territorial becoming and belonging in a grassroots approach from across India, studying them in culturally sensitive ways to recover local life-worlds and their self-understanding. Further, challenging the stereotypical bracketing of the mythical with the sacred and the material with the historical, the multidisciplinary essays in the book examine myth in relation to not only religion but other historical phenomena such as ecology, ethnicity, urbanism, mercantilism, migration, politics, tourism, art, philosophy, performance, and the everyday. This book will be of interest to scholars and general readers of Indian history, regional studies, cultural geography, mythology, religious studies, and anthropology.